ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TARIKAN PENGUNJUNG PUSAT PERBELANJAAN DI KOTA MAKASSAR (STUDI KASUS MALL PANAKKUKANG DAN TRANS MALL) - Qarnila R Rahman (Journal Techno Entrepreneur Acta, 2020)
With the rapid development and the rise of the city's economy, causing a real impact on the trade sector, this is one of the causes of the rapid development and growth of shopping centers. The number of new shopping centers has sprung up and the development of old shopping centers has led to the emergence of problems in the field of transportation (movement systems such as generation and traction) and harmony in land use patterns. The problem of infrastructure and means of transportation in a city that often experiences a mismatch between what is needed and what is available. One form of travel that occurs in urban areas is a trip to the shopping center. The same thing happened to Panakkukang Mall and Trans Mall shopping centers. This study aims to determine the factors that influence people to travel to Panakkukang Mall and Trans Mall as well as a mathematical model of the attraction of shopping center infrastructure. Data collection techniques by means of surveys and direct interviews using a structured questionnaire list. The population in this study were people who visited Panakkukang Mall and Trans Mall shopping centers. Sampling is done by simple random sampling technique. The data analysis technique is done by using multiple linear regression approach.